Glucosylsphingosine is a key biomarker of Gaucher disease. Issue 11 (8th August 2016) - Murugesan, Vagishwari; Chuang, Wei‐Lien; Liu, Jun; Lischuk, Andrew; Kacena, Katherine; Lin, Haiqun; Pastores, Gregory M.; Yang, Ruhua; Keutzer, Joan; Zhang, Kate; Mistry, Pramod K.
Abstract : Gaucher disease (GD) involves the accumulation of glucosylceramide (GL1) and its deacylated lysolipid, glucosylsphingosine (lyso‐GL1) which is implicated in mediating immune dysregulation and skeletal disease. The aim of our study was to assess plasma Lyso‐GL1 as a biomarker of GD and its response to therapy. Plasma lyso‐GL1 in 169 patients with GD type 1 (GD1) was measured by LC‐MS/MS. Significant predictors of plasma LGL1 were assessed by Pearson's correlation coefficient, Wilcoxon Mann Whitney test and multiple linear regression. Propensity scores were used to match patients on treatment mode: Enzyme Replacement Therapy (ERT) vs. Eliglustat Tartrate SRT (ELI‐SRT). Plasma Lyso‐GL1 levels in healthy controls averaged 1.5 ng/ml (1.3–1.7; 95% CI). In untreated GD patients, the levels were massively elevated (180.9 ng/ml: 95% CI, 145.4–216.5) and imiglucerase ERT resulted in marked reduction (89 ng/ml: 95% CI, 69.2–129.4) ( P  < 0.001). Lyso‐GL1 correlated with chitotriosidase ( r  = 0.59 P  < 0.001), CCL18 ( r  = 0.62 P <0.001), hepatomegaly ( r  = 0.28 P  < 0.001), splenomegaly ( r  = 0.27 P  = 0.003), splenectomy ( P  = 0.01) and treatment mode ( P  < 0.001). By multiple linear regression, the strongest predictors of lyso‐GL1 were age ( P  < 0.001), splenectomy ( P  = 0.02), Chitotriosidase ( P  < 0.001) and CCL18 levels ( P  = 0.001). After propensity score matching to obtain comparable groups of patients on ERT vs ELI‐SRT, lyso‐GL1 levels were lower among patients receiving ELI‐SRT by 113 ng/ml (95% CI: 136–90.3 ng/ml P  < 0.001). Plasma lyso‐GL1 is a key biomarker of GD. ERT reduced lyso‐GL1 levels. By propensity scoring, ELI‐SRT resulted in greater reduction of lyso‐GL1 than ERT. Am. J. Hematol. 91:1082–1089, 2016. © 2016 Wiley Periodicals, Inc.